Temporal and Spatial Changes in Phyllosphere Microbiome of Acacia Trees Growing in Arid Environments - Al Ashhab, Ashraf; Meshner, Shiri; Alexander-Shani, Rivka; Dimerets, Hana; Brandwein, Michael; Bar-Lavan, Yael; Winters, Gidon (Frontiers in Microbiology, 2021)
Background: The evolutionary relationships between plants and their microbiomes are of high importance to the survival of plants in general, and even more in extreme conditions. Changes in the plant’s microbiome can affect plant development, growth, fitness and health. Along the arid Arava, southern Israel, acacia trees (Acacia raddiana and Acacia tortilis) are considered keystone species. In this study, we investigated the ecological effects of plant species, microclimate, phenology and seasonality on the epiphytic and endophytic microbiome of acacia trees. One hundred and thirty-nine leaf samples were collected throughout the sampling year and were assessed using 16S rDNA gene amplified with five different primers (targeting different gene regions) and sequenced (150 bp paired-end) on an Illumina MiSeq sequencing platform. Results: Epiphytic bacterial diversity indices (Shannon-Wiener, Chao1, Simpson and observed number of OTUs), were found to be nearly double compared to endophyte counterparts. Epi- and endophyte communities were significantly different from each other in terms of the composition of the microbial associations. Interestingly, the epiphytic bacterial diversity was similar in the two acacia species but the canopy sides and sample months exhibited different diversity, while the endophytic bacterial communities were different in the two acacia species but similar throughout the year. Abiotic factors, such as air temperature and precipitation, were shown to significantly affect both epi- and endophytes communities. Bacterial community compositions showed that Firmicutes dominate Acacia raddiana and Proteobacteria dominate Acacia tortilis; these bacterial communities consisted of only a small number of bacterial families, mainly Bacillaceae and Comamonadaceae in the endophyte for A. raddiana and A. tortilis, respectively, and Geodematophilaceae and Micrococcaceae for epiphyte bacterial communities respectively. Interestingly, about 60% of the obtained bacterial classification were unclassified below family level (i.e., “new”). Conclusions: These results shed light on the unique desert phyllosphere microbiome highlighting the importance of multiple genotypic and abiotic factors in shaping the epiphytic and endophytic microbial communities. This study also shows that only a few bacterial families dominate both epi- and endophyte communities, highlighting the importance of climate change (precipitation, air temperature and humidity) in affecting arid land ecosystems where acacia trees are considered keystone species.